Community Health Promotion by Three Aor Two Sor Principle, Wang Somboon Sub-district, Sakaeo Province - Yanti, Nadchar; Chusak, Thassaporn; Khuneepong, Apichai (Area Based Development Research Journal, 2020)
This participatory research aims to promote healthy behaviors among local people in Wang Somboon sub-district, Wang Somboon district, Sakaeo province, by practicing the principle of Three Aor Two Sor as a major guideline. The research process employed 4 steps: 1) the researchers conducted a field study to collect data on local community’s capacity; 2) a civil societal forum was organized to address health problems, particularly those concerning excessive weights against standard; 3) a network was established to carry out research to identify activity guidelines; and 4) four activities under the Three Aor Two Sor principle were implemented, which included healthy eating education, exercise for good health, effective ways to kill stress, and saying goodbye to alcohol and smoking. The data are interpreted and recommendations were suggested for joint activity development. The sample group included 51 local people in Wang Somboon sub-district participating in 4 Three Aor Two Sor activities. Subsequently, a follow-up on health conditions among the participants was conducted. The findings indicated that 37 out of 40, lost weight while the normal weight group increased from 9 to 12. The research conclusions are as follows: 1) established the health promotion network in Wang Somboon sub-district; 2) applied the principle of Three Aor Two Sor and health promotion activities to improve the health of the samples in this area; and 3) implemented the strategies and guidelines of health promotion such as pamphlets on appropriate eating habits and initiating the Three Aor Two Sor Day, which highlights good health among people in local communities for life.